Artificial Ageing of Paper: Scientific Foundations, Methodological Framework, and Applications in Archival and Library Preservation - Zervos, Spiros (Journal of Integrated Information Management, 2025)
Purpose - This paper presents the theoretical basis, methodological framework, and practical applications of artificial ageing of paper, a key technique for predicting and improving the long-term stability of archival and library materials. It aims to familiarize conservators, archivists, and librarians with the fundamental concepts necessary for interpreting scientific literature and making informed preservation decisions. Design/methodology/approach - The article introduces key chemical mechanisms of paper ageing, particularly acid hydrolysis and oxidation of cellulose. It presents standardized accelerated ageing methods and discusses two core indicators of paper degradation: degree of polymerization and folding endurance. Mathematical models are employed to explain ageing rates and reaction kinetics, including Arrhenius-based estimations of useful paper lifespan. Experimental setups for artificial ageing and comparative evaluations of conservation treatments are illustrated using both real and hypothetical data. Findings - This article synthesizes well-established scientific knowledge and practical methods related to artificial ageing of paper. By organizing complex concepts into an accessible framework, it clarifies how artificial ageing can be used to assess paper stability, evaluate conservation interventions, and understand the influence of environmental conditions. The discussion reinforces widely accepted conclusions in the field, such as the impact of acidity, the role of deacidification, and the value of alkaline-buffered materials. Originality/value - This paper is intended as both a practical reference and an educational tool. It bridges scientific methodology and conservation practice, offering a synthesis of theory, standards, and field applications. It enhances the scientific literacy of preservation professionals and supports evidence-based conservation and storage decisions. The clear mathematical modeling of degradation processes makes the content accessible even to readers without advanced technical backgrounds. Practical implications - The synthesis presented here can guide practitioners in selecting conservation treatments, evaluating storage materials, and establishing preservation conditions to help extend the lifespan of archival holdings.